(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
As is known, adjectives are a group of words that express the characteristics of creatures and objects-events. Such adjectives are used to express various forms of an object, signs of shape and form. Adjectives that express color are prone to compounding. The compounding feature in them, in particular, creates semantic diversity and shifted meanings. Adjectives meaning color in Old Turkic language have the characteristic of semantic fluency. The topic studied in the article is dedicated to determining the scope of adjectives meaning color used in the ancient Turkic language and studying the adjectives from both linguistic and artistic-aesthetic point of view.